Religiusitas, Konflik Gender, dan Pencegahan Kekerasan terhadap Perempuan dan Anak di Kota Sorong - Rais, Lukman; Ramli, Umar; Pattisahusiwa, Fitriani; Hidaya, Nur; Maqfirah, Ariani (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2025)
The purpose of this study is to examine (1) how religious groups can help to avoid violent conduct, (2) how religion and violence are related, and (3) how gender conflict and violent behavior are related. In Sorong City, Southwest Papua, this study employs a quantitative methodology using a correlational design and probability sampling approaches. Cluster random sampling was used to determine the sample. Gathering information via surveys, literature reviews, and observation combined with descriptive and inferential statistical analysis. The results of the study found that religious institutions play a role in preventing violence against women and children through teaching-based education that emphasizes protection and peace. The hypothesis test results showed that religiosity did not significantly affect violent behavior (tcount -0.459 < ttable 1.960; significance 0.647 > 0.05). On the other hand, when combined with gender conflict, religiosity showed a significant effect (fcount 616.697 > fttable 3.04; significance 0.001 < 0.05). This study also revealed that gender conflict was positively and significantly related to violent behavior (tcount 31.665 > ttable 1.960; significance 0.000 < 0.05), indicating that gender inequality and gender role stereotypes exacerbate violence.